A Feline HFpEF Model with Pulmonary Hypertension and Compromised Pulmonary Function. Issue 1 (December 2017) - Wallner, Markus; Eaton, Deborah; Berretta, Remus; Borghetti, Giulia; Wu, Jichuan; Baker, Sandy; Feldsott, Eric; Sharp, Thomas; Mohsin, Sadia; Oyama, Mark; von Lewinski, Dirk; Post, Heiner; et al.
Abstract Heart Failure with preserved Ejection Fraction (HFpEF) represents a major public health problem. The causative mechanisms are multifactorial and there are no effective treatments for HFpEF, partially attributable to the lack of well-established HFpEF animal models. We established a feline HFpEF model induced by slow-progressive pressure overload. Male domestic short hair cats (n = 20), underwent either sham procedures (n = 8) or aortic constriction (n = 12) with a customized pre-shaped band. Pulmonary function, gas exchange, and invasive hemodynamics were measured at 4-months post-banding. In banded cats, echocardiography at 4-months revealed concentric left ventricular (LV) hypertrophy, left atrial (LA) enlargement and dysfunction, and LV diastolic dysfunction with preserved systolic function, which subsequently led to elevated LV end-diastolic pressures and pulmonary hypertension. Furthermore, LV diastolic dysfunction was associated with increased LV fibrosis, cardiomyocyte hypertrophy, elevated NT-proBNP plasma levels, fluid and protein loss in pulmonary interstitium, impaired lung expansion, and alveolar-capillary membrane thickening. We report for the first time in HFpEF perivascular fluid cuff formation around extra-alveolar vessels with decreased respiratory compliance. Ultimately, these cardiopulmonary abnormalities resulted in impaired oxygenation. Our findings support the idea that this model can be used for testing novel therapeutic strategies to treat the ever growing HFpEF population.